AUTOMATED ACCOUNTING PRACTICES IN CAMEROONIAN ACCOUNTING FIRMS: A QUALITATIVE STUDY OF ATTITUDE AND ADOPTION - Pafe Bruno Ndong; Elle Narcisse (Malete Journal of Accounting and Finance, 2024)
This research is motivated by growing strength of artificial intelligence particularly automation of accounting practices in the world at large and Cameroonian accounting firms, in particular. This has led to a growing threat of change which has an impact on the accountant’s professional role and attitude. The purpose of the study is to examine the impact of automation on accountants’ practices in accounting firms. The qualitative research method is used and the data was collected through semi-structured interviews. Interpretation of the interviews was through thematic analysis method. 12 accountants make up the study sample from a population of 35 accountants in the city of Douala, Littoral region of Cameroon. The study finds that the automation of accounting process is more efficient and beneficial. However, it has increased the risks of faults, loss of control and jobs, a change in the employment structure, skills, and competence. The attitudes of the accountant are positive towards automation but the fear of loss of jobs and obsolete IT skills are present. The study concludes that automated accounting practices is efficient and effective and has a significant impact on accountants. It therefore recommends that accountants should be ready to adapt to the current trends, develop interdisciplinary skills in education and competence. Also, firms should put control measures and regulatory policies in place to prevent excessive use of automation.